Challenges and Solutions in Religious Guidance for Converts (muallaf) in Tanjung Beringin, Tanah Karo - Lubis, M. Alif Erhanda; Abdurrahman, Zulkarnain (Jurnal Sosiologi Agama Indonesia (JSAI), 2024)
This study investigates the primary challenges and potential solutions in the religious guidance of converts (muallaf) in Tanjung Beringin Village, Tanah Karo, North Sumatra. Utilizing a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation. This study showed that the absence of continuous religious guidance, combined with the lack of permanent da’i, has weakened the religious understanding and enthusiasm among the converts. Additionally, parental neglect in supporting their children's religious education exacerbates this issue. The study proposes several solutions, including establishing collaborations with Islamic organizations and da'wah institutions to provide alternating da’i, appointing permanent Islamic religious instructors, revitalizing basic Islamic studies, and enhancing parental involvement in religious education. These measures aim to strengthen the religious identity and resilience of the convert community against external influences.